Influence of twisted tape inserts on energy and exergy performance of an evacuated Tube-based solar air collector. (1st September 2021) - Veera Kumar, A.; Arjunan, T.V.; Seenivasan, D.; Venkatramanan, R.; Vijayan, S.; Matheswaran, M.M.
Highlights: Analytically studied the effect of ten different TT inserts on performance of ETIBSAC. Heat transfer enhancement is observed for all configurations of twisted tape inserts. Loose-Fit Perforated Twisted Tape exhibits better energy effectiveness. Minimum twist ratio and hole diameter ratio of LFPTT delivers better performance. Maximum η e f f of LFPTT with (y/D) = 2 & (d/D) = 0.0714 is 56.48% at 300 kg/h. Abstract: Energy and exergy behaviour of an Evacuated Tube with Inserted Baffles Solar Air Collector (ETIBSAC) with various design configurations of twisted tape is analyzed through an analytical model. Among those configurations, Loose-Fit Perforated Twisted Tape (LFPTT) exhibits better performance in terms of energy effectiveness. Hence, LFPTT was selected for further investigation to identify the influence of helical twist ratio (y/D) and tape hole diameter ratio (d/D). The analytical model predicts the energy and exergy performance of the ETIBSAC with LFPTT inserts (y/D) = 2, 2.5 and 3 & (d/D) = 0.0714, 0.107 and 0.143. The results show that ETIBSAC with LFPTT produces the highest effective thermal and exergy efficiencies at lower airflow rates. The peak thermal efficiency of 62.33% was attained at 400 kg/h with (y/D) = 2 & (d/D) = 0.0714. The exergy efficiency attained its peak value of 3.91% and reduces with increasing airflow rate due to more exergy destruction. It is concluded that the proposed insertion of twisted tapes can be adopted for enhancing the performance of the system.